Use of Fossil Bryozoans in Sourcing Lithic Artifacts. Issue 5 (4th August 2014) - Key, Marcus M.; Jackson, Patrick N. Wyse; Falvey, Lauren W.; Roth, Barbara J.
<x xml:space="preserve">Abstract</x> This study reviews the occurrence and potential of bryozoans within lithic artifacts and also sets out a methodology for their use in sourcing and discusses the advantages and disadvantages of this approach. We present case studies from our own research and from the literature on using bryozoans in sourcing archaeological lithic artifacts. Fossil bryozoans of different ages and clades can be effectively used to determine the material source of lithic artifacts from a variety of prehistoric ages. The case studies included in this report span the stratigraphic range of bryozoans from the Ordovician to the Neogene. The bryozoans came from four different orders: trepostome, fenestrate, cyclostome, and cheilostome. The use of these lithic artifacts ranged back to 25 ka. Although the majority of the fossil bryozoans were incidental in the artifacts, the bryozoans were still useful for determining their original source rock. The improved searchable online paleontologic databases allow for more efficient use of fossil bryozoans to constrain the stratigraphic and paleogeographic distribution of source outcrops. Although generally underutilized in sourcing prehistoric lithic artifacts, it is clear that by analyzing bryozoans, an increased understanding of the lithologic nature of these materials could be gained by the archaeological community.